Tris(ethylenediamine)cobalt(II) sulfate - Yotnoi B. (2014)
The structure of the title compound, [CoII(C2H 8N2)3]SO4, the cobalt example of [M(C2H8N2)3]SO4, is reported. The Co and S atoms are located at the 2d and 2c Wyckoff sites (point symmetry 32), respectively. The Co atom is coordinated by six N atoms of three chelating ethyl-enediamine mol-ecules generated from half of the ethyl-enediamine mol-ecule in the asymmetric unit. The O atoms of the sulfate anion are disordered mostly over two crystallographic sites. The third disorder site of O (site symmetry 3) has a site occupancy approaching zero. The H atoms of the ethyl-enediamine mol-ecules inter-act with the sulfate anions via inter-molecular N - H⋯O hydrogen-bonding inter-actions.